Pengaruh Pemberian Insentif dan Disiplin Kerja terhadap Kinerja Pegawai di Badan Kepegawaian Daerah Sumatera Selatan - Akbar, Junior; Susi Handayani; Roswaty (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2025)
This study aims to analyze the influence of providing incentives and work discipline both partially and significantly on employee performance at the South Sumatra Regional Civil Service Agency. This type of research is quantitative descriptive. The population used in the inbi study is the total number of employees of the South Sumatra Regional Civil Service Agency. The technique of determining the number of samples uses saturated sampling which is the entire population used in the research sample, which is as many as 70 respondents. Data analysis used data quality tests, classical assumption tests, and multiple linear regression analysis with t-test (partial), F test (simultaneous), and R-test. Work discipline has a positive and significant effect on the performance of used car employees at the South Sumatra Regional Civil Service Agency. The provision of incentives and work discipline simultaneously has a positive and significant effect on the performance of employees at the South Sumatra Regional Civil Service Agency.